Effects of renal denervation on insulin resistance. (November 2012) - Hering, Dagmara; Esler, Murray D; Schlaich, Markus P
Hypertension and diabetes are recognized as two major comorbidities accounting for the greatest proportion of cardiovascular morbidity and mortality. Despite the availability of safe and effective pharmacological therapies, the percentage of patients achieving optimal blood pressure and glycemic control remains unsatisfactory. The contribution of sympathetic activation to the development and maintenance of systemic hypertension and comorbidities is well recognized. Aside from several novel pharmacological approaches, catheter-based sympathetic renal denervation (RDN) has gained a significant role in treatment-resistant hypertension and has recently been introduced to clinical practice. Preliminary data indicate that aside from better blood pressure control, RDN may also be associated with a reduction in fasting glucose and insulin levels, as well as improvements in the Homeostasis Model Assessment (HOMA) index. If these observations are confirmed in larger controlled clinical trials, RDN may emerge as a preferred treatment option for patients with resistant hypertension and concomitant alterations of glucose metabolism.